2021
DOI: 10.1001/jamahealthforum.2021.2131
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Outcomes With Bundled Payments Among Hospitalized Patients Attributed to Accountable Care Organizations

Abstract: IMPORTANCEIt is unknown how outcomes are affected when patients receive care under bundled payment and accountable care organization (ACO) programs simultaneously. OBJECTIVE To evaluate whether outcomes in the Medicare Bundled Payments for Care Improvement (BPCI) program differed depending on whether patients were attributed to ACOs in the Medicare Shared Savings Program. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted using Medicare claims data from January 1, 2011, to September 30, 2016, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Safety-net hospitals reported lower participation in value-based payment prior to COVID when compared to other hospitals. Although there was no significant difference between groups in decreasing or suspending these efforts during COVID, to the extent that participation in these payment models is associated with improvements in care and outcomes, 34 these differences are notable. Since many value-based and alternative payment models were suspended during the pandemic, the long-term impact on participation remains to be seen.…”
Section: Discussionmentioning
confidence: 82%
“…Safety-net hospitals reported lower participation in value-based payment prior to COVID when compared to other hospitals. Although there was no significant difference between groups in decreasing or suspending these efforts during COVID, to the extent that participation in these payment models is associated with improvements in care and outcomes, 34 these differences are notable. Since many value-based and alternative payment models were suspended during the pandemic, the long-term impact on participation remains to be seen.…”
Section: Discussionmentioning
confidence: 82%
“…Geriatric hospitals, if modeled after successful geriatric models, should be able to do this better than typical adult hospitals. Also, health care systems that participate as an Accountable Care Organization with bundled payments may find geriatric hospitals beneficial since some of the cost savings with geriatric models of care can occur after discharge, for example related to increased likelihood of discharge home instead of a facility and reduced readmission rates ( Deschodt et al, 2013 ; Flood et al, 2013 ; Navathe et al, 2021 ; Palmer, 2018 ).…”
Section: Challengesmentioning
confidence: 99%
“…All other measures of medical testing increased as was envisioned [47]. Furthermore, the use of institutional postdischarge facilities was successfully reduced [50]. The model negatively impacted performance on total spending, medical specialist and medication spending, but post discharge spending and primary care spending were curbed [46,47,49,50].…”
Section: Disease-based Bundled Paymentsmentioning
confidence: 99%
“…Furthermore, the use of institutional postdischarge facilities was successfully reduced [50]. The model negatively impacted performance on total spending, medical specialist and medication spending, but post discharge spending and primary care spending were curbed [46,47,49,50]. One qualitative study [48] mapped other consequences and found some positive effects (better collaboration, greater transparency, and better process quality) but also some negative ones (increased administrative burden, greater price variations, and unwanted dominance by GP care groups).…”
Section: Disease-based Bundled Paymentsmentioning
confidence: 99%
See 1 more Smart Citation